Search for the radiative Ξ b − $$ Ξ_b^{-} $$ → Ξ − γ decay - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellán Beteta; T. Ackernley; B. Adeva; M. Adinolfi; H. Afsharnia; C. A. Aidala; S. Aiola; Z. Ajaltouni; S. Akar; et al. (Journal of High Energy Physics, 2022)
Abstract The first search for the rare radiative decay Ξ b − $$ Ξ_b^{-} $$ → Ξ − γ is performed using data collected by the LHCb experiment in proton-proton collisions at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 5.4 fb −1. The Ξ b − $$ Ξ_b^{-} $$ → Ξ − J/ψ channel is used as normalization. No Ξ b − $$ Ξ_b^{-} $$ → Ξ − γ signal is found and an upper limit of B $$ \mathcal{B} $$ ( Ξ b − $$ Ξ_b^{-} $$ → Ξ − γ) < 1.3 × 10 −4 at 95% confidence level is obtained.